2004
DOI: 10.1023/b:jogc.0000018824.04992.7b
|View full text |Cite
|
Sign up to set email alerts
|

Family Environments of Women Seeking BRCA1/BRCA2 Genetic Mutation Testing: An Exploratory Analysis

Abstract: Although there is some understanding of the shared characteristics and predictors of psychological distress of women participating in hereditary breast and ovarian cancer registries, these same characteristics are only beginning to be identified in research on community women seeking genetic testing for BRCA1/BRCA2 gene mutations. This study provides an initial exploration of characteristics associated with family environments for 51 community women waiting to receive such genetic testing results. Thirty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Family communication regarding hereditary cancer and family support during genetic testing may be more essential for hereditary cancer distress and cancer worry. Indeed, in two studies that addressed family functioning in genetic counseling, family functioning was only related to satisfaction with hereditary cancer genetic counseling (40) and general distress (41).…”
Section: Discussionmentioning
confidence: 99%
“…Family communication regarding hereditary cancer and family support during genetic testing may be more essential for hereditary cancer distress and cancer worry. Indeed, in two studies that addressed family functioning in genetic counseling, family functioning was only related to satisfaction with hereditary cancer genetic counseling (40) and general distress (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, to date few studies have examined the relationship between family characteristics and the actual decision to use genetic testing. It has been suggested that an unsupportive family environment has been associated with low rates of testing . However, more information is necessary in order to provide decision support to families who harbor cancer‐predisposing mutations.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…15 A proband may provide social support and be open, or instead be closed, nonsupportive and avoidant in the communication. 3,[15][16][17] These communication processes between proband and relative could be influenced by family-relational characteristics such as level of openness to discuss cancer. 1,2,18 Fourth, relatives recall and interpret the information that the proband has communicated about their cancer risks and heredity likelihood.…”
Section: General Family Communication Timelinementioning
confidence: 99%